Effect of visitor and visit variables on overall satisfaction in three visitor institutions - Yalowitz, Steven Spencer, author; Loomis, Ross J., advisor (Colorado State University. Libraries, 2001)
One of the most important outcome variables for visitor institutions is satisfaction (i.e., whether or not visitors are satisfied with their experiences). Consumer literature links satisfaction to repeated purchases. In museums, satisfaction leads to positive word-of-mouth, which, in turn leads to increased visitation (Adams, 1988). While satisfaction has been thoroughly researched in consumer science and in marketing, museum visitor studies specifically examining satisfaction and its antecedents are few and far between. The purpose of the present study was to determine whether visitor or visit variables are the best predictors of satisfaction, whether the predictive power of these variables would differ in different types of visitor institutions, and if higher ratings of satisfaction would result in specific visitor outcomes after the visit. The present study examined and compared the major predictors of visitor satisfaction in an art museum, a nature and science museum, and an aquarium. The four main types of variables studied were visitor variables, visit variables, satisfaction for the visit, and visitor intentions and other outcomes. Visitor variables included as a person's Need For Sensory Experience (NSE; Eisenberger, Sucharkski, Yalowitz, Rhoades, & Loomis, 2001), Need for Cognition (NFC; Cacioppo & Petty, 1982), and informational and sensory reasons for visiting. Informational Reasons for Visiting consisted of learning new things and expanding one's knowledge, while Sensory Reasons for Visiting were to have vivid visual experiences and see visually interesting exhibits. The visit variables studied were the visitor ratings of perceived informational and sensory opportunities during the visit. Satisfaction (the dependent measure) was evaluated using an item asking about a visitor's overall satisfaction with their visit. The current study revealed that a combination of both visit and visitor variables best predicted satisfaction, although satisfaction is regressed on only four of the six key variables: Sensory Opportunities, Informational Reasons for Visiting, Informational Opportunities, and Sensory Reasons for Visiting. In addition, some interaction terms of the key variables added additional variance: Informational Reasons for Visiting x Informational Opportunities, Informational Reasons for Visiting x Sensory Reasons for Visiting, and Need For Sensory Experience x Informational Reasons for Visiting. The first two interaction terms were negative interactions while the last was positive. Satisfaction significantly increased visitor outcome variables such as likelihood of a return visit, likelihood of recommending friends and family visit, willingness to provide a quote to be used for endorsement, and perceiving that an institution cared about them. This type of research will allow researchers and museum professionals to understand and increase visitor satisfaction, as well as determining what role the visitor and the institution play in satisfaction. By understanding and improving satisfaction, visitors will be more loyal, recommend visits to others, and be more likely to return.
Keywords: social psychology